1992
DOI: 10.1148/radiology.185.1.1523309
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial invasion by endometrial carcinoma: assessment with plain and gadolinium-enhanced MR imaging.

Abstract: A prospective study was designed to determine the sensitivity and specificity of nonenhanced T2-weighted and contrast material-enhanced T1-weighted magnetic resonance (MR) imaging in assessing the depth of myometrial invasion in patients with proved endometrial cancer. In 56 consecutive patients with clinically determined early-stage disease, findings of the two MR imaging techniques were compared with results of histologic examination of surgical specimens. Myometrial invasion was classified as absent (stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
2
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 0 publications
9
67
2
3
Order By: Relevance
“…To date, the combination of dynamic contrast material-enhanced (DCE) and T2-weighted MR imaging has been accepted as the examination with the highest accuracy for staging of endometrial cancer. This protocol has been implemented by most European cancer centers and is also recommended in the European Society of Urogenital Radiology Endometrial Cancer Staging guidelines (5,9,14). However, the added benefit of diffusion-weighted imaging (DWI) (15) and quantitative methods have been described in studies of other pelvic cancers (16,17), especially in rectal and cervical cancer (17)(18)(19).…”
Section: Author Contributionsmentioning
confidence: 99%
“…To date, the combination of dynamic contrast material-enhanced (DCE) and T2-weighted MR imaging has been accepted as the examination with the highest accuracy for staging of endometrial cancer. This protocol has been implemented by most European cancer centers and is also recommended in the European Society of Urogenital Radiology Endometrial Cancer Staging guidelines (5,9,14). However, the added benefit of diffusion-weighted imaging (DWI) (15) and quantitative methods have been described in studies of other pelvic cancers (16,17), especially in rectal and cervical cancer (17)(18)(19).…”
Section: Author Contributionsmentioning
confidence: 99%
“…Treatment and prognosis depend on several factors, including stage, tumour grade, depth of myometrial penetration, cervical penetration and nodal metastasis (Manfredi et al 2004;Kinkel et al 1999;Hricak et al 1991;Sironi et al 1992a).…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic abnormal bleeding occurs in about 80% of patients, and most of the cases are diagnosed in an early-stage (Sironi et al 1992a), and cured (Lien et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is no consensus in the literature regarding the added value of DCE-MRI in staging of endometrial cancer. Although the majority of the published studies demonstrate that the addition of multiphase DCE-MRI to T2W imaging leads to a significant improvement in the accuracy of assessment of the deep myometrial invasion [8,9,[11][12][13][14][15], some authors have found no significant difference [16,17].…”
mentioning
confidence: 99%